Spolne vloge v samoupravnem delavskem tisku - Opassi, Oskar (Zgodovinski časopis, 2022)
The article presents the thematisation of gender roles in the Delamaris workers’ newsletter between 1974 and 1990. By limiting the times-pan, the analysis refers to the period after the introduction of the 1974 Constitution, which declaratively transferred the lever of form-ing the relations within enterprises to their employees. This was expected to lead to the formation of “ideal” socialist relations; how-ever, in practice, these changes inhibited the workers’ involvement in the decision-making within enterprises. The employees’ testimonies allow for a presentation of the balance between the conceptual goals of socialist self-managing and the workers’ actual day-to-day life. The article thus highlights the gender relations and the specific nature of workers’ periodicals as a historical source.
Keywords: Delamaris; delavski tisk; gender roles; glasila; Odnosi med delodajalci in delojemalci; Samoupravljanje; self-managing relations; Socializem; Spolne vloge v delovnem okolju; Tisk; worker's periodicals